2022
DOI: 10.1142/s0219265921430325
|View full text |Cite
|
Sign up to set email alerts
|

AI Intelligence Chatbot to Improve Students Learning in the Higher Education Platform

Abstract: The integrated chatbot for artificial intelligence customizes the learning experience for the students in higher education platform. The chatbot tests the answers of the students and offers insights for the students to improve their learning skills. Further, It helps to improve students’ thinking ability and expectations in higher education platform. The demanding factors for the students in the higher education platform include the need for interactive learning in a non-linear world, enhancing the thinking ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 21 publications
0
11
1
1
Order By: Relevance
“…Sandu and Gide (2019) also found that AI chatbots enhance communication, productivity, and efficient teaching and learning assistance. The AI chatbots further make higher education students' learning experience customizable, answer their questions and curiosities, and advance their learning abilities and skills (Liu, Subbareddy & Raghavendra, 2022). The thinking ability needs and expectations of students and academicians in higher education are improved through AI chatbots in making learning fun and interesting in providing access to innovative knowledge and skills.…”
Section: Discussion Of the Findings Ai Chatbots Usage In Hementioning
confidence: 99%
“…Sandu and Gide (2019) also found that AI chatbots enhance communication, productivity, and efficient teaching and learning assistance. The AI chatbots further make higher education students' learning experience customizable, answer their questions and curiosities, and advance their learning abilities and skills (Liu, Subbareddy & Raghavendra, 2022). The thinking ability needs and expectations of students and academicians in higher education are improved through AI chatbots in making learning fun and interesting in providing access to innovative knowledge and skills.…”
Section: Discussion Of the Findings Ai Chatbots Usage In Hementioning
confidence: 99%
“…Works, such as those composed by Chen et al (2023), Liu et al (2022), andOdden et al (2023), also examined the potential impact of GenAI on the learner experience, with a prevailing notion of Ge-Volumen 52 número 4, octubre-diciembre, 2023 / págs. 401-409 Peter Bannister, Alexandra Santamaría Urbieta, Elena Alcalde Peñalver nAI taking on the role of learning assistant as opposed to educator replacement found to be in common amongst findings.…”
Section: Effects Of Genai On He Student Learningmentioning
confidence: 99%
“…Teaching methods and modes are the key factors determining teaching effectiveness and are the structural framework combining the teaching content []- [20]. Figure 1 shows the current problems in English teaching.…”
Section: Analysis Of University English Teaching Modementioning
confidence: 99%